Uji Farmakognostik dan Identidikasi Senyawa Pada Beberapa Tingkatan Fraksi Ekstrak Etanol Daun Lengkuas (Alpinia Galanga) - Yanti Saubari; Kunti Nastiti; Mambang Mambang (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
ABSTRACT Background:Galangal Leaves (Alpinia Galanga) is a plant that grows in Indonesia. This plant is used as a cleaning wound after childbirth, bathing water for rheumatism sufferers, and as stimulation. Objective: To find out about the results of Pharmacognostic Tests and Identification of Compounds at Several Levels of The Ethanol Extract Fractions of Galangal Leaves (Alpinia Galanga) Method: extraction process using maceration method with 70% ethanol solvent was carried out for 3 x 24 hours, evaporated with rotary vacuum evaporator until thick extract was then fractionated with different solvents and detected by secondary metabolites using color test and KLT method Results: Macroscopic tests included a slippery green color with a length of 40cm, width 8cm, flat edge, pointed tip, blunt leaf base, and crossing. Microscopic test is the presence of epidermis, parenchyma, and stomata. Results Physico-chemical parameters of drying shrinkage were 0.23%, extracts of solvents with certain solvents were water-soluble and ethanol-soluble were 0.405% and 0.395%. Phytochemical screening results of the compounds obtained in the n-hrxane fraction, ethyl acetate fraction, and methanol fraction are steroids, tannins, phenolics, terpanoids, alkaloids, saponins, and flavanoids. KLT results for the n-hexane fraction with a mobile phase of methanol: ammonium (5: 0.25) with a spray of red brick (alkaloid). Conclusion: pharmacognostic testing meets the requirements and extracts of Galangal Leaves (Alpinia Galanga)